2021
DOI: 10.2147/prbm.s318657
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Empathy on the Attentional Processing of Painful and Emotional Stimuli

Abstract: Background Empathy is shown to affect the attentional processing of painful stimuli and emotional stimuli. However, whether the attentional effects on emotional stimuli depend on emotional valence and the nature of the relationship between the attentional effects on different stimuli are still unknown. Methods In the present study, 25 high-empathy (HE) participants and 25 low-empathy (LE) participants were recruited to perform dot-probe tasks on painful stimuli and emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…The findings of the current study were in line with the findings of Bi et al. ( 2021 ) and Pilch et al. ( 2020 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The findings of the current study were in line with the findings of Bi et al. ( 2021 ) and Pilch et al. ( 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…Specifically, similar to Bi et al. ( 2021 ) who found significant positive association between empathy and selective attention to pain‐related information (i.e., images others’ different body parts in painful situations), significant correlation was found between higher empathy and greater selective attention to pain‐related information (pain faces) in the current study. Moreover, in line with Pilch et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, a stronger reaction to the patient's negative emotions might bias the therapist's attention towards the more emotionally salient or intense topics during the sessions, narrowing their focus. Quite in fact, it has been shown that more empathic subjects (1) show an attentional bias towards painful facial stimuli (Yan et al, 2016), ( 2) have more difficulty disengaging from painful stimuli (Bi et al, 2021), and (3) experience stronger emotional interference effects in stroop tasks (Thompson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%